2016
DOI: 10.1038/srep21117
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and plasticity of the epithelial to mesenchymal transition induced by miR-200 family inhibition

Abstract: Whereas miR-200 family is known to be involved in the epithelial-to-mesenchymal transition (EMT), a crucial biological process observed in normal and pathological contexts, it has been largely unclear how far the functional levels of these tiny RNAs alone can propagate the molecular events to accomplish this process within several days. By developing a potent inhibitor of miR-200 family members (TuD-141/200c), the expression of which is strictly regulatable by the Tet (tetracycline)-On system, we found using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…C). Taken together, these findings were consistent with previous reports of EMT suppression by miR‐200b …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…C). Taken together, these findings were consistent with previous reports of EMT suppression by miR‐200b …”
Section: Resultssupporting
confidence: 93%
“…It has been reported that iR‐200 family members inhibit EMT via downregulation of ZEB1/2 . We firstly determined the relative expression level of miR‐200b in seven HCC cell lines by quantitative RT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The miR-200 family of miRNAs consists of five members grouped in two independent transcriptional clusters: miR-200a, -200b, and -429, located on chromosome 1p36, and miR-200c and -141, located on 12p13 18 . MiR-200c is the predominant member of the miR-200 family, which suppresses the epithelial-mesenchymal transition (EMT), and the downregulation of miR-200 family members in some tumors promotes invasion and metastasis 19 - 21 . Song and colleagues found that miR-200c inhibits breast cancer proliferation by targeting KRAS 22 .…”
Section: Introductionmentioning
confidence: 99%